MENGENAL BANTUAN HUKUM MELALUI PENDAPAT PARA AHLI HUKUM - Arliman S, Laurensius (Ensiklopedia Sosial Review, 2025)
Abstract: Legal aid is an important aspect of the legal system which aims to provide access to justice for all individuals, especially those who are less fortunate. This concept is applied in various forms in different countries, with approaches ranging from government legal aid programs to services provided by non-governmental organizations and pro bono lawyers. Even though it still faces many challenges in its implementation, efforts to expand access to legal aid must continue to be made in order to create a fairer and more inclusive legal system.Keywords: Assistance, Law.